Reforms and job quality: the case of the elder-care sector. (1st April 2010) - ,
Abstract : In the last decade, all European countries have introduced regimes for care of the elderly as they have striven to adapt to demographic and social change. Meanwhile, labour market reforms have deeply changed the national employment models in which these care regimes are embedded, increasing labour market segmentation and wage inequality. This paper presents an analysis of the impact of these policy changes on the main features of elder-care labour markets. It is argued, first, that the characteristics of each country's elder-care sector mirror the general features of its national employment model. And second, that the way in which care reforms are implemented in the various countries reflects and somehow reinforces the general features of its care regime, in terms of the division of labour between formal and informal care and of the quantity and quality of care work.